The Formation of Charles Taze Russell's Religious Identity - Орловський Роман Володимирович (My University, 2025)
The dissertation research examines the origins and development of the religious identity of the founder of the Watchtower Society and the International Bible Students movement, Charles Taze Russell. Today in Ukraine there are religious communities operating that are descendants of the International Bible Students movement and consider C. Russell as their ideological founder, who laid the foundations for the teachings that they profess and disseminate today. Foremost, we are talking about the organization of Jehovah's Witnesses, widely represented in the religious space of Ukraine. Moreover, several modern Bible Students movements exist worldwide, emphasizing their affiliation with the teachings of C. Russell. This is, in particular, the community of Bible Students called the Missionary Movement <Epiphany=, which has its representation mainly in the western regions of Ukraine. In domestic religious studies, attention is drawn to the teachings and practices of Jehovah's Witnesses; However, it should be noted that the studies of Ukrainian scientists concern, foremost, the modern development of this organization. At the same time, an important aspect of the study of any religious movement is an overview of not only the current state, but also the first stages of development and the preconditions for its emergence. It should be noted that there is only a small amount of scientific works that would thoroughly describe the formation of the religious views of C. Russell. For this reason, the study of the development of the religious identity of the figure who led to the emergence of this religious movement is becoming relevant. In addition, the religious organization of Jehovah's Witnesses and their founder are mentioned among many confessional sources of various Christian denominations. C. Russell is presented there as a controversial figure who led to the emergence o teachings that deny or challenge the fundamental doctrines professed by most traditional Christian churches. The choice of the topic is due to the fact that, despite the visibility of the teaching thanks to the heirs of the International Bible Students movement, the genesis of the views and the formation of the personality of the founder have been analyzed quite little. This is, in particular, due to the fact that C. Russell's books and articles are not published by Jehovah's Witnesses. Only the Missionary Movement <Epiphany= distributes both printed and video products containing articles and books by this religious figure in Ukrainian, but in limited quantities. The aim of the research is to conduct a comprehensive religious studies analysis of the formation and development of C. Russell's religious identity, the origins of his confessional beliefs and activities as the founder and leader of the Watchtower Society. The dissertation research examines the essence of the religious identity of C. Russell in historical genesis, paying attention to the main life milestones of his autobiographical narrative that influenced his teaching, the desire to rethink Christian teaching, in particular in the context of a return to biblical sources, an apocalyptic revision of traditional dogmas and the beginning of a community of like-minded people and active missionary work. By using a significant amount of archival sources and known methodological techniques, a religious studies research of the formation of views that are today spread through Jehovah's Witnesses and Bible Students was conducted. The heterogeneous nature of Adventism in the 19th century is considered, the position of the founder of the Watchtower Society regarding Protestantism in general, and Millerism and Adventism in particular is reflected. It is important to consider the attitude of C. Russell to the problem of religious nationalism and the observance of civil and religious freedom. The work consists of thematic blocks that reveal the stated goal of the research. The first chapter contains the theoretical and methodological part of the research. The primary methods for achieving the aim and completing the objectives of the dissertation research are considered, and an analytical survey of literary sources is conducted. The concept of religious identity is analyzed, and the problem of confessional identification of C. Russell in the context of the development of the religious organization of Jehovah's Witnesses is highlighted. The historical context of the religious situation in the USA in the 19th century, which had a direct impact on the formation of C. Russell's worldview, is studied. The second chapter is devoted to the study of the biographical features of the formation of C. Russell as a religious figure. The circumstances of the formation of his religious views are traced, the character traits of C. Russell that determined the direction of his spiritual quest are highlighted. The significance of religious faith in the formation of his spiritual experience is studied. The key areas of the missionary activity of the Watchtower Society during C. Russell's leadership are highlighted, in particular the mass publication of the Watchtower magazine and the six-volume series <Millennial Dawn=, the publication of sermons in secular publications, as well as the creation and screening of the film project <Photo-Drama of Creation= and its abridged audio version <Eureka Drama=. Two missionary visits of C. Russell to the territory of Ukraine and Moldova are described. The visit to Chisinau and Odessa was accompanied by his assessment of the influence of the Russian autocracy on the society of that time. And the events associated with C. Russell9s visit to Lviv allowed for a comparison of the level of religious freedom in the Ukrainian lands at the end of the 19th 3 beginning of the 20th centuries, which were part of the Russian and Austro- Hungarian empires. In the third chapter, the research direction is aimed at clarifying the religious identity of C. Russell by analyzing his attitude to Protestantism, the Reformation and Adventism. It has been established that the views of this religious figure can be attributed to Protestant restorationism. The aspects of Adventism that C. Russell approved of, but about which he expressed disagreement, are highlighted. C. Russell's attitude to the Millerite movement and its founder is considered. The study of terminological markers made it possible to trace the historical continuity of C. Russell's movement from the ideas of Millerism and Adventism, which he personally denied. The origin of the name of the Watchtower magazine is analyzed, as well as the problem associated with the identification of the International Bible Students movement with Adventism in the public consciousness. An analysis is performed to assess the reliability of statements from various confessional sources regarding the influence of Seventh-day Adventist teachings on C. Russell's religious views. The attitude of C. Russell to the political and social spheres of public life is studied separately from the point of view of his religious worldview. The attitude towards the phenomenon of American religious nationalism with an emphasis on care in ensuring the foundations of civil and religious freedom is highlighted. It was found that the religious leader did not see the possibility for his fellow believers to occupy government positions and participate in politics. C. Russell also cited a number of circumstances regarding why participation in voting is unacceptable for International Bible Students. Regarding the performance of military duty, C. Russell, under certain conditions, allowed the legality of following army orders, while emphasizing that it is unacceptable to violate the biblical order prohibiting murder. In matters of protecting labor rights, C. Russell points out that participation in trade unions and the exercise of the right to strike are permissible subject to compliance with legal grounds.

Дисертаційне дослідження присвячене витокам та розвитку релігійної ідентичності засновника Товариства Вартової Башти та руху Міжнародних дослідників Біблії Чарльза Тейза Рассела. Сьогодні в Україні звершують свою діяльність релігійні спільноти, які є нащадками руху Міжнародних дослідників Біблії та вважають Ч. Рассела своїм ідейним засновником, який заклав основи вчення, яке сьогодні вони сповідують і поширюють. Насамперед мова йде про організацію Свідків Єгови, яка широко представлена у релігійному просторі України. Також у світі існує низка рухів сучасних Дослідників Біблії, які підкреслюють свою приналежність до вчення Ч. Рассела. Це, зокрема спільнота Дослідників Біблії під назвою Місійний рух «Епіфанія», що має своє представництво переважно у західних областях України. У вітчизняній релігієзнавчій науці звернено увагу на вчення та практики Свідків Єгови; проте варто зазначити, що дослідження українських вчених стосуються, перш за все, сучасного розвитку цієї організації. Водночас важливим аспектом для дослідження будь-якого релігійного руху є огляд не тільки сучасного стану, а також перших етапів розвитку та передумов його появи. Варто зазначити, що існує тільки незначний обсяг наукових праць, які б ґрунтовно описували формування релігійних поглядів Ч. Рассела. З цієї причини набуває актуальності дослідження розвитку релігійної ідентичності постаті, яка спричинила появу цього релігійного руху. Крім того, релігійна організація Свідків Єгови та постать їхнього засновника згадуються серед багатьох конфесійних джерел різних християнських деномінацій. Ч. Рассел там представлений як контроверсійна особистість, яка спричинила появу вчень, які заперечують або кидають виклик основоположним доктринам, які сповідує більшість традиційних християнських церков. Вибір теми обумовлений тим, що, незважаючи на помітність вчення завдяки спадкоємцям Міжнародних дослідників Біблії, генеза поглядів та формування особистості родоначальника проаналізовані досить мало. Це, зокрема, зумовлене тим, що книги та статті Ч. Рассела не публікуються Свідками Єгови. Тільки Місійний рух «Епіфанія» поширює як друковану, так і відеопродукцію, що містить статті та книги цього релігійного діяча українською мовою, однак в обмеженій кількості. Метою дослідження є проведення всебічного релігієзнавчого аналізу становлення та розвитку релігійної ідентичності Ч. Рассела, витоків його конфесійних переконань та діяльності як засновника та лідера Товариства Вартової Башти. У дисертаційному дослідженні розглянуто сутність релігійної ідентичності Ч. Рассела в історичній генезі, звернено увагу на основні життєві віхи його автобіографічного наративу, що впливали на його вчення, на прагнення переосмислити християнське вчення, зокрема у контексті як повернення до біблійних джерел, апокаліптичних та есхатологічних уявлень, перегляд традиційних догматів так і започаткуванні спільноти однодумців та проведенні активної місіонерської діяльності. При залученні значного об'єму архівних джерел та послуговуючись відомими методологічними прийомами, здійснено релігієзнавче дослідження формування поглядів, які сьогодні поширюються через Свідків Єгови та Дослідників Біблії. Розглянуто неоднорідну природу адвентизму XIX ст., відображено позицію засновника Товариства Вартової Башти щодо протестантизму загалом, та міллеризму й адвентизму зокрема. Важливим є розгляд ставлення Ч. Рассела до проблеми релігійного націоналізму та дотримання громадянської та релігійної свободи. Робота складається з тематичних блоків, що розкривають поставлену мету дослідження. Перший розділ містить теоретико-методологічну частину дослідження. Розглянуто основні підходи для досягнення мети та виконання завдань дисертаційного дослідження, а також було здійснено аналітичний огляд літературних джерел. Проаналізовано поняття релігійної ідентичності та висвітлено проблему конфесійної ідентифікації Ч. Рассела у контексті розвитку релігійної організації Свідків Єгови. Досліджено історичний контекст релігійної ситуації в США у XIX ст., що мав безпосередній вплив на формування світогляду Ч. Рассела. Другий розділ присвячений вивченню біографічних особливостей становлення Ч. Рассела як релігійного діяча. Простежено обставини формування його релігійних поглядів, виокремлено риси характеру Ч. Рассела, які визначили напрямок його духовних пошуків. Досліджено значення релігійної віри у формуванні його духовного досвіду. Виокремлено ключові напрями місіонерської роботи Товариства Вартової Башти за часів керівництва Ч. Рассела, зокрема масове видання журналу «Вартова Башта» та шеститомника «Світанок Тисячоліття», публікації проповідей у світських виданнях, а також створення та показ кінопроєкту «Фото-драма сотворення» і її скороченої аудіоверсії «Драма Еврика». Описано два місіонерські відвідування Ч. Расселом території України та Молдови. Відвідини Кишинева та Одеси супроводжувались його оцінкою впливу російського самодержавства на тогочасне суспільство. А події, пов’язані з відвідуванням Ч. Расселом Львова, дозволили здійснити порівняння рівня релігійної свободи на українських землях наприкінці XIX – на початку XX століть, які входили до складу Російської та Австро-Угорської імперій. У третьому розділі напрямок дослідження спрямований на уточнення релігійної ідентичності Ч. Рассела шляхом аналізу його ставлення до протестантизму, Реформації та адвентизму. Встановлено, що погляди цього релігійного діяча можна віднести до протестантського реставраціонізму. Виокремлено аспекти адвентизму, які Ч. Рассел схвалював, та щодо яких висловлював незгоду. Описано ставлення Ч. Рассела до міллеритського руху та постаті його засновника. Дослідження термінологічних маркерів дозволило простежити історичну спадкоємність руху Ч. Рассела від ідей міллеризму та адвентизму, що він особисто заперечував. Проаналізовано історію появи назви журналу «Вартова Башта», а також проблему, пов’язану з ототожненням руху Міжнародних дослідників Біблії з адвентизмом у суспільній свідомості. Проведено аналіз правдивості тверджень низки конфесійних джерел про вплив вчення Церкви адвентистів сьомого дня на релігійні погляди Ч. Рассела. Окремо вивчено ставлення Ч. Рассела до політико-соціальних царин суспільного життя з точки зору його релігійного світогляду. Висвітлено ставлення до феномена американського релігійного націоналізму з наголосом на турботу в забезпеченні засад громадянської та релігійної свободи. Зʼясовано, що релігійний діяч не бачив для своїх одновірців можливості обіймати державні посади та участі у політиці. Також Ч. Рассел наводив низку обставин щодо того, чому участь у голосуванні для Міжнародних дослідників Біблії є неприпустимою. Щодо виконання військового обов’язку Ч. Рассел за певних умов допускав правомірність виконання армійських наказів, водночас акцентуючи, що недопустимо порушувати біблійний наказ про заборону вбивства. У питаннях захисту трудових прав Ч. Рассел вказує на те, що участь у профспілкових об’єднаннях та реалізація права на страйк є допустимими за умов дотримання законних підстав.
Формування релігійної ідентичності Чарльза Тейза Рассела
Keywords: Чарльз Тейз Рассел; релігійна віра; Товариство Вартової Башти; Дослідники Біблії; Свідки Єгови; протестантизм; протестантські церкви; міллеритський рух; адвентизм; Церква Адвентистів сьомого дня; релігійний націоналізм; військова служба; громадянська та релігійна свобода; зв’язок Ч. Рассела з Україною.; Charles Taze Russell; religious faith; Watchtower Society; Bible Students; Jehovah's Witnesses; Protestantism; Protestant churches; Millerite movement; Adventism; Seventh-day Adventist Church; religious nationalism; military service; civil and religious freedom; C. Russell's connection with Ukraine.